An institutional approach to appropriation and provision in the commons : a case study in the Highlands of Eritrea - Habteab Sibhatu, Adam (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MAgric (Agricultural Economics))—University of Stellenbosch, 2006.